2012
DOI: 10.1111/j.1365-2583.2012.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the citrus red mite, Panonychus citri, and its gene expression by exposure to insecticide/acaricide

Abstract: The citrus red mite, Panonychus citri, is known for its ability rapidly to evolve resistance to insecticides/acaricides and to adapt to hosts that produce toxins. In this study, we constructed an unprecedented four gigabase pair transcriptome of P. citri, which was assembled into 64 149 unique transcripts, the functions of which were annotated by five public databases. A total of 116 unique transcripts were identified as representatives of potential involvement in the detoxification of xenobiotics. Genes recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 61 publications
3
47
0
1
Order By: Relevance
“…Among them, cytochromes P450 (CYPs), carboxylesterases (CCEs), glutathione S-transferases (GSTs), UDP-glucuronosyl transferases (UGTs) enzymes, as well as ABC transporters were found differentially expressed between resistant and susceptible strains to pyrethroids1617183031. Likewise, induced up-regulation of detoxifying genes was found in resistant individuals exposed to pyrethroids, such as in the mosquito Anopheles gambiae 30, the cattle tick Rhipicephalus (Boophilus) microplus 32 or the mosquito Culex quinquefasciatus 2425, as well as in susceptible individuals, such as in Panonychus citri 19, Liposcelis bostrychophila 20, and Melita plumulosa 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, cytochromes P450 (CYPs), carboxylesterases (CCEs), glutathione S-transferases (GSTs), UDP-glucuronosyl transferases (UGTs) enzymes, as well as ABC transporters were found differentially expressed between resistant and susceptible strains to pyrethroids1617183031. Likewise, induced up-regulation of detoxifying genes was found in resistant individuals exposed to pyrethroids, such as in the mosquito Anopheles gambiae 30, the cattle tick Rhipicephalus (Boophilus) microplus 32 or the mosquito Culex quinquefasciatus 2425, as well as in susceptible individuals, such as in Panonychus citri 19, Liposcelis bostrychophila 20, and Melita plumulosa 21.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies that have focused on single time-points showed that the exposure of individuals to toxicants induces up-regulation of several genes, while several others are down-regulated161718192021. However, these are single snapshots of the defense response that do not allow us to know if and how the differentially expressed genes are modulated during toxicant exposure.…”
mentioning
confidence: 99%
“…The results of genome analysis showed that the delta and mu classes of GSTs exist as large gene clusters in two spotted spider mite GST superfamilies, but no epsilon class of GSTs has been identified in this species [12]. Moreover, 24 Unigene transcripts belonging to seven classes (delta, kappa, mu, omega, sigma, theta and zeta) have been identified from the transcriptome data of Panonychus citri [13]. Comparatively, in insects, GST superfamily genes have been clearly classified into at least six classes, including delta, epsilon, omega, sigma, theta and zeta [14].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we identified 24 unique GST transcripts from annotation of the P. citri transcriptome [13]. To further characterize the molecular responses of GST genes to acaricides/insecticides in P. citri , in the current study we further obtained seven full-length GST cDNAs and carried out a detailed analysis of these genes.…”
Section: Introductionmentioning
confidence: 99%
“…is similar to findings from previous transcriptomic analyses of a variety of different taxa. These include studies of other spiders (e.g., [31,33,76]), other arachnids (e.g., [8,83,84]), other metazoans (e.g.,[53,85,86]), and even non-metazoans (e.g., [87,88]). One previously suggested explanation for these similarities (e.g., [7]) is that transcriptome assemblies from short-read RNA-Seq analyses are biased toward the capture of highly expressed, conserved housekeeping genes.…”
Section: Resultsmentioning
confidence: 99%